Pengaruh Big Five Personality Trait terhadap Prokrastinasi Akademik Penyelesaian Skripsi Mahasiswa Universitas Negeri Padang - Rizkia, Faradilla; Nurmina, Nurmina (Lembaga Yasin AlSys, 2025)
This study aims to examine the influence of the Big Five Personality Traits on academic procrastination in thesis completion among students at Universitas Negeri Padang. A quantitative approach was used, with proportional random sampling to select a sample of 259 students from the 2018–2020 cohorts who had enrolled in the thesis course for at least one year. The instruments employed included the IPIP-BFM-50 scale to measure the five personality dimensions and an academic procrastination scale to assess the level of task delay. Data were analyzed using multiple linear regression. The results revealed that among the five personality dimensions, only neuroticism had a significant effect on academic procrastination in thesis completion. This indicates that students with higher neuroticism scores tend to exhibit greater tendencies to postpone academic tasks, including thesis work. These findings highlight the importance of considering personality traits in academic mentoring strategies and stress management interventions for students.